2023
DOI: 10.3390/biology12030399
|View full text |Cite
|
Sign up to set email alerts
|

Osteonal Microcracking Pattern: A Potential Vitality Marker in Human Bone Trauma

Abstract: In forensic anthropology, the differential diagnosis between peri- and postmortem bone fractures is mainly based on macroscopic criteria. In contrast, studies focusing on bone histology are very scarce. In a recent publication, we showed that (perimortem) fractures in fresh human bones exhibit a different osteonal microcracking pattern than (postmortem) damage in dry bones. In the current work, we explored whether this osteonal microcracking pattern is distinctive of the vitality of (perimortem) fresh bone fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…It has been well documented that approximately 80 to 90% of MCKs are located in the broad and brittle interstitial area of the cortical bone as it is easier for them to initiate there due to the presence of large hydroxyapatite crystals, reduced osteocyte density, and limited bone remodelling [15,16,27,28]. Nevertheless, Ebacher et al [12], Winter-Buchwalder et al [15], and Schwab et al's [16] studies have all noted the presence of microcracking patterns related with bone trauma and highlighted the importance of focusing on osteonal MCKs in fresh fracture histological analysis [15]. The results of our study on osteonal microcrack damage, when comparing GST and BFT traumatic death cases, showed that total osteonal damage is greater in GST despite the difference not being significant.…”
Section: Osteonal Damage Extentmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been well documented that approximately 80 to 90% of MCKs are located in the broad and brittle interstitial area of the cortical bone as it is easier for them to initiate there due to the presence of large hydroxyapatite crystals, reduced osteocyte density, and limited bone remodelling [15,16,27,28]. Nevertheless, Ebacher et al [12], Winter-Buchwalder et al [15], and Schwab et al's [16] studies have all noted the presence of microcracking patterns related with bone trauma and highlighted the importance of focusing on osteonal MCKs in fresh fracture histological analysis [15]. The results of our study on osteonal microcrack damage, when comparing GST and BFT traumatic death cases, showed that total osteonal damage is greater in GST despite the difference not being significant.…”
Section: Osteonal Damage Extentmentioning
confidence: 99%
“…As highlighted in previous papers, there is a need for further investigation into osteonal microcracking patterns since osteonal MCKs specifically have been associated with fresh fractures [12,15,16]. So far, there has not been a focus on osteonal microcracking patterns in relation to trauma type but only literature on BFT cases and trauma timing [14][15][16]. These studies have demonstrated that in fresh BFT cases, a higher proportion of osteonal MCKs can be observed when compared to dry bone which has greater interstitial MCKs [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations